Enhancing competences for competitive advantage - Sanchez, Ron; Heene, Aimé (Emerald, 2010)
This volume explores ways in which an organization's existing competences can be enhanced as sources of competitive advantage - either enduring or intendedly transitional. Competence enhancing activities considered include political lobbying to extend the lifetime and value of a firm's competences, expanding services to enhance the value of manufacturing capabilities, initiating knowledge management projects, strategically adapting a firm's governance structures to take advantage of government policy initiatives, staging development of competences in internationalization processes, improving capabilities in managing alliances, understanding the factors conducive to entrepreneurial action-taking, and using individual competency development in self-managing processes for organizational competence building.
Description based on print version record.
Keywords: Competition.; Core competencies.; Business planning.; Strategic planning.; elektronické knihy; electronic books